Advanced composite material simulation - Oller,S. (2008)
A computational methodology is presented for modeling the non-linear mechanical behavior of composite structures made of FRP (Fiber-Reinforced Polymers) laminates. The model is based on the appropriate combination of the constitutive models of compounding materials, considered to behave as isolated continua, together with additional closure equations that characterize the micro-mechanics of the composite from a morphological point of view. To this end, any appropriate constitutive model may be selected for each phase. Each component is modeled separately and the global response is obtained by assembling all contributions taking into account the interactions between components in a general phenomenological way. To model the behavior of a single uni-directional (UD) composite laminated, a Serial-Parallel continuum approach has been developed assuming that components behave as parallel materials in the fibers alignment direction and as serial materials in orthogonal directions. Taking into account the internal morphology of the composite material, it is devised a strategy for decoupling and coupling component phases. This methodology [Rastellini 2006], named "compounding of behavior", allows to take into consideration local non linear phenomenon in the compounding materials, like damage, plasticity, etc. in a coupled manner. It is based on the proper management of homogenous constitutive models, already available for each component. In this way, it is used all developments achieved in constitutive modeling for plain materials, what makes possible the transference of this technology to composites. A laminated theory complemented with the proposed UD model is employed to describe the mechanical behavior of multi-directional laminates. A specific solution strategy for the general non linear case is proposed. It provides quick local and global convergences, what makes the model suitable for large scale structures. The model brings answers on the non-linear behavior of composites, where classical micro-mechanics formulas are restricted to their linear elastic part. The methodology is validated through several numerical analyses and contrasted against experimental data and benchmark tests.